Adverse skin reactions of healthcare workers using N95 mask and latex gloves at Kasih Ibu Denpasar General Hospital Bali Indonesia during coronavirus disease 2019 (COVID-19) pandemic – a descriptive study - Firly Clarissa Suyanto; Ariana Ariana; Ni Made Dwi Puspawati (Intisari Sains Medis, 2021)
Introduction: Corona virus disease 2019 (COVID-19), caused by SARS-CoV-2, was first identified in Wuhan, Hubei Province, China in December 2019. World Health Organization (WHO) then officially declared the disease as a global pandemic in March 2020. It has rapidly spread throughout the world, causing a huge burden to the health sector. With the increasing number of cases, healthcare workers (HCWs) were exposed to the regular use of personal protective equipment (PPE) such as N95 masks, latex gloves, and gowns. As a result of long term use of PPE, many adverse skin reactions may occur. Hence, this study aims to determine the adverse skin reactions among healthcare workers using PPE.Method: This study is a cross-sectional descriptive study conducted at Kasih Ibu Denpasar General Hospital Bali Indonesia. Questionnaires were used for the research. A total of 45 valid questionnaires were collected, with the majority being women (88.9%) and with an age range of 20 – 30 years old (55.6%).Result: The result showed that the most common adverse skin reactions among HCWs wearing N95 masks were indentation and ear pain (73.3%) and nasal bridge scarring (48.9%). The most common adverse skin reactions among HCWs wearing latex gloves were dry skin (46.7%) and skin soaked with sweat (17.8%).Conclusion: Our study explored the adverse skin reactions due to long term use of PPE, N95 mask and latex gloves in particular. These adverse skin reactions are mostly mild because they continue using PPE.